Gestão da demanda na indústria automotiva: o papel da integração interfuncional - Freitas, Marlos Rocha de (2017)
The literature on supply chain management indicates that cross-functional integration is necessary to achieve external integration with suppliers. In addition, it can be a necessary tool to bring together the demand and supply areas (DSI), and such an initiative can ease disputes and improve the efficiency of the entire supply chain. The DSI literature, presented the importance of the cross-functional integration for the efficiency of these processes. However, it does not focus on the functions involved, nor does it define how integration can be operationalized. Thus, there is little emphasis on the operational and technical aspects of cross-functional integration as a managerial tool. The objective of this study is to analyze how internal and external integration contribute to the realization of demand processes, and how they generate impacts on supply activities in an automotive supply chain. To reach this proposal, a case study was carried out with three links in the supply chain of a brazilian subsidiary of a multinational vehicle manufacturer. In all, 16 in-depth interviews were conducted with vehicle assembler managers and their suppliers and resellers. As results, it was identified that, in the first link, there is strong interaction and joint planning between the suppliers and the internal areas of the manufacturer, related to planning and production control (PCP), internal logistics and product development. The analysis of the second link, which refers to internal integration within the manufacturer itself, shows that although there are many areas with good inter-functional integration, the best integrative practices occur within the same board. Although there are frequent meetings and the occurrence of some actions that approximate the marketing / sales, logistics and production functions, the level of integration between these areas is not satisfactory. The third link, which involves the external integration between dealers and the manufacturer, presented an excellent relationship between the retailers and the company analyzed. This shows a good integration, because the manufacturer's business area has tools to generate leads and direct them to resellers CRM. This case study allowed us to identify that external integration, both on the demand side, with retailers and on the supply side, in relation to suppliers, occurs at a higher level and with higher quality than internal integration within the analyzed company. External integration in the supply chain studied was more efficient and intense than the internal integration in the manufacturer, showing that it may be possible to achieve external integration before internal integration. This research identified that Joint planning, willingness to work together and group spirit were the most efficient tools to generate positive impacts on the organization and that factors such as cross-functional meetings, job rotation and support from top management can present good results to improve the level of integration and improve management processes, since the oscillations of demand are the main causes of conflicts between functional areas. Finally, this work suggests that cross-functional integration must be embedded in strategic planning and organizational culture, to transform organizations into more skilled competitors.